Communication systems within SMRT tunnel - Yap, Danny Jian Huang (Nanyang Technological University, 2020)
This study uses ESMD Device to capture the spectrum occupancy along the train tracks in Singapore during operation hour. Discone Antennas were mounted at the front and rear car of the train, during the spectrum monitoring test conducted along the North South Line from Ulu Pandan Depot to Marina South Pier Station, and along the East West Line from Tuas Train Depot to Pasir Ris Station. This was to capture the spectrum occupancy during normal operation hour to find out how much interfering source were present. The results from the spectrum monitoring test will aid in the study of tunnel propagation modeling. From the result, we can determine how much the CBTC system is affected due to multipath propagation in the train tunnel. This study also involves the creation of website that consist of different calculators to carry out different computations for radio communication link. The calculators were coded using JavaScript and implemented on the website for user to carry out the necessary computation. Aside from the website, Android Application for mobile phone was also created using Android Studio. It has different calculators that can carry out the same computation available on the website. The purpose is to provide convenience for user who are at work site such as train tunnel, as most of the people will carry a mobile phone around. This mobile application will provide the user with a mean to carry out the necessary computation.